2006
DOI: 10.1245/aso.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Mapping of the Gastrointestinal Tract by Using Invisible Light

Abstract: We report the use of invisible near-infrared light for intraoperative sentinel lymph node mapping of the GI tract. This technology overcomes the limitations of currently available methods, permits patient-specific imaging of lymphatic flow and sentinel nodes, and provides highly sensitive, real-time image-guided dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 20 publications
3
99
0
Order By: Relevance
“…Optical imaging using NIR fluorescent lymphatic tracers provides real-time assessment of lymphatic flow from the point of injection to the SLN(s), relatively high sensitivity due to the penetrating ability of NIR photons, and elimination of the need for radioactivity. NIRFI has been validated in large animal models for SLN mapping of skin [16,17], lung [21], esophagus [22], pleural space [22], GI tract [16,21], and spontaneous melanoma [23]. Our study of invasive bladder cancer confirms that the anatomy of lymphatic flow is highly variable among individuals, and can involve structures such as the urachus and presacral nodes, and that SLN mapping must be performed on an individual basis.…”
Section: Discussionsupporting
confidence: 55%
“…Optical imaging using NIR fluorescent lymphatic tracers provides real-time assessment of lymphatic flow from the point of injection to the SLN(s), relatively high sensitivity due to the penetrating ability of NIR photons, and elimination of the need for radioactivity. NIRFI has been validated in large animal models for SLN mapping of skin [16,17], lung [21], esophagus [22], pleural space [22], GI tract [16,21], and spontaneous melanoma [23]. Our study of invasive bladder cancer confirms that the anatomy of lymphatic flow is highly variable among individuals, and can involve structures such as the urachus and presacral nodes, and that SLN mapping must be performed on an individual basis.…”
Section: Discussionsupporting
confidence: 55%
“…QDs may possess significant advantages over current methods to label transplanted cells, which have been hampered by both safety issues (e.g., the use of engineered viruses as vectors) and the ability of cells to reliably and permanently express a given factor (e.g., the use of liposomes or naked DNA). Experiments outside of the nervous system have demonstrated that QDs may be superior in certain human diagnostic clinical applications such as the identification of tumor-positive sentinel lymph nodes (Kim et al, 2004;Soltesz et al, 2005Soltesz et al, , 2006. Our in vivo demonstration of the lack of toxicity using the developing embryo and nervous system support the further exploration of QDs as diagnostic and therapeutic tools for human disease.…”
Section: Applications Of Qdsmentioning
confidence: 59%
“…Recently, there have been clinical imaging studies using the FDA-approved dye indocyanine green (ICG) for detection of sentinel lymph nodes in patients with gastric, 15 intrathoracic, 16,17 and lung cancer. 18 Surgical oncologists are currently investigating mapping regional metastasis by fluorescent optical imaging using ICG, noncovalently bound to human serum albumin.…”
Section: Discussionmentioning
confidence: 99%